Retrospective Evaluation of Surgical Anatomical Repair of Distal Biceps Brachii Tendon Rupture Using Suture Anchor Fixation - Witkowski, Jarosław (Med Sci Monit, 2017)
BACKGROUND: To date, no consensus has been reached regarding the preferred fixation method to use in the repair of distal biceps brachii tendon rupture. The aim of this study was to clinically and functionally (Mayo Elbow Performance Index, MEPI) assess the upper limb after surgical anatomic reinsertion of the distal biceps brachii tendon with the use of suture anchor fixation method with regard to postoperative time and limb dominance, and to assess postoperative complications. MATERIAL/METHODS: The sample comprised 18 males (age 52.09±8.89 years) after surgical anatomical distal biceps brachii reinsertion using suture anchor fixation. A comprehensive clinical and functional evaluation and pain assessment were performed. RESULTS: In terms of postoperative complications, an isolated case of surgical site sensory disturbances was noted. Circumferences (p-value 0.21–1.00) and ROM (p-value 0.07–1.00) were similar in the operated and nonoperated limbs. The isometric torque (IT) values of muscles flexing and supinating the forearm were comparable in both limbs (p-value 0.14–0.95), but in patients with the operated dominant limb, the mean IT value was not higher than the value obtained in the nonoperated nondominant one. The MEPI indicated good and excellent results (80.00±15.00–90.00±8.66 points), but a detailed individual analysis showed that reported scores were not in line with objectively measured features. CONCLUSIONS: The results of the comprehensive retrospective evaluation justify the clinical use of suture anchors fixation method in the surgical anatomical reinsertion of a ruptured distal biceps brachii tendon. The assessment of a patient should always report both subjective and objective measures.